School Peer Non-academic Skills and Academic Performance in High School - Gregory J. Palardy (Frontiers in Education, 2019)
Research shows that students' non-academic attributes, such as forms of engagement, dispositions, and social and emotional skills, are associated with a range of outcomes—including academic performance. However, little research has investigated the effects of school peer non-academic attributes on academic performance. This study begins to address this gap in the research literature by examining the effects of 10 measures of school peer non-academic attributes. Importantly, most of the non-academic attributes examined in this study are malleable through school-based interventions. The results show that five measures of school peer attributes have medium to large effects on academic performance, including collaboration skills (a social-emotional characteristic), conscientiousness and belonging (dispositions), and cognitive and behavioral engagement. In contrast, the corresponding effects of students' own non-academic attributes were uniformly smaller. These findings indicate that the non-academic attributes of one's school peers play an important role in academic performance above and beyond one's own non-academic attributes. These results suggest that school-wide interventions and instructional practices designed to improve the non-academic skills of all students will provide additional benefits compared with interventions focusing on students with the most under-developed non-academic attributes.